2018
DOI: 10.1101/498378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species Tree Inference on Data with Paralogs is Accurate Using Methods Intended to Deal with Incomplete Lineage Sorting

Abstract: Received ...; reviews returned ...; accepted ...Abstract.---The multispecies coalescent (MSC) has emerged as a powerful and desirable framework for species tree inference in phylogenomic studies. Under this framework, the data for each locus is assumed to consist of orthologous, single-copy genes, and heterogeneity across loci is assumed to be due to incomplete lineage sorting (ILS). These assumptions have led biologists that use ILS-aware inference methods, whether based directly on the MSC or proven to be st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 75 publications
(135 reference statements)
1
41
0
Order By: Relevance
“…Their study has an advantage over our study in that it explored larger datasets (up to 500 species), but they did not consider ASTRAL, and all their genes evolved under a strict molecular clock. Another study [10] evaluated ASTRAL-multi on true gene trees, and found it had very high accuracy. Overall, our study is the first study to explore ASTRAL-multi on estimated gene trees.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their study has an advantage over our study in that it explored larger datasets (up to 500 species), but they did not consider ASTRAL, and all their genes evolved under a strict molecular clock. Another study [10] evaluated ASTRAL-multi on true gene trees, and found it had very high accuracy. Overall, our study is the first study to explore ASTRAL-multi on estimated gene trees.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated methods on simulated datasets based on the 16-taxon fungal dataset studied in [10,25]. We used this fungal dataset to construct a model species tree, on which we generated gene trees using SimPhy [20] under three GDL rates (the lowest of which is the one selected by [25] to reflect the fungal dataset, so that the higher two reflect more challenging conditions).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations